The Effectiveness of Using Story Circle In Teaching Writing - Fransiska, Fini Widya (Universitas Islam Negeri Raden Intan Lampung, 2016)
The study is aimed to find out whether there is significant difference in writing ability who are taught by using story circle and who are taught by using free writing. This research is an experimental research. The experimental research involves experimental (VIII.4) group and control group B(VIII.3) of 32 students of the eighth grade students of SMP N 1Pringsewu in academic year 2014/2015. Both classes were given pre-test. Then, the students give the treatment after that both groups were given post-test. Then, for collecting data the researcher applied writing test and analyzed the data by using t-test. The research finding of the research shows that there is any significant difference to writing ability between the students who are taught using story circle and those who are taught using free writing of Junior High School students. After the treatment, the mean is 71.50, the standard deviation is 9.795, the df is 62, and the value of the significance was 0.045 smaller than 0.05. If the significance is smaller than 0.05, its means that hypothesis is accepted. Therefore, it can be concluded that using story circle in teaching writing could improve the students to write. Story circle is a technique to motivate the students in learning English, especially in teaching writing.